Oxidation is an underappreciated post-translational modification in the regulation of immune responses associated with changes in phosphorylation - Karkossa, Isabel; Fürst, Sabine; Großkopf, Henning; von Bergen, Martin; Schubert, Kristin (Frontiers in Immunology, 2023)
Although macrophages are known to be affected by their redox status, oxidation is not yet a well-recognized post-translational modification (PTM) in regulating macrophages and immune cells in general. While it has been described that the redox status of single cysteines in specific proteins is relevant for macrophage functions, global oxidation information is scarce. Hence, we globally assessed the impact of oxidation on macrophage activation using untargeted proteomics and PTM-omics. We exposed THP-1 macrophages to lipopolysaccharide (LPS) for 4 h and 24 h and applied a sequential iodoTMT labeling approach to get information on overall oxidation as well as reversible oxidation of cysteines. Thus, we identified 10452 oxidation sites, which were integratively analyzed with 5057 proteins and 7148 phosphorylation sites to investigate their co-occurance with other omics layers. Based on this integrative analysis, we found significant upregulation of several immune-related pathways, e.g. toll-like receptor 4 (TLR4) signaling, for which 19 proteins, 7 phosphorylation sites, and 39 oxidation sites were significantly affected, highlighting the relevance of oxidations in TLR4-induced macrophage activation. Co-regulation of oxidation and phosphorylation was observed, as evidenced by multiply modified proteins related to inflammatory pathways. Additionally, we observed time-dependent effects, with differences in the dynamics of oxidation sites compared to proteins and phosphorylation sites. Overall, this study highlights the importance of oxidation in regulating inflammatory processes and provides a method that can be readily applied to study the cellular redoxome globally.